Ho‘oulu Me Ke Ikaika: A Community-Support Group that Improves Long-Term Emotional and Social Health of Adolescent and Young Adult Survivors of Childhood Cancer - Maile Enos; Kiyomi Goto; Joyce Wong; Patricia W. Nishimoto; Erin O. Bantum; Ian Pagano; Dianne Fochtman; Paulette M. Yamada (Journal of Adolescent and Young Adult Oncology, 2026)
Purpose: Survivors of childhood cancer have unique needs, requiring tailored psychosocial support. To ascertain the effectiveness of a community-based survivorship group’s services on changes in emotional and social self-efficacy, perceived purpose and meaning in life, loneliness, and post-traumatic growth from pre- to postretreat among minority adolescent and young adult (AYA) survivors over a 2-year period. Methods: Two annual residential retreats were attended by 15 and 13 AYA survivors, respectively. Experiential learning activities that fostered connection, self-reflection, and resilience were provided. Inventories assessing meaning/purpose (Patient-Reported Outcomes Measures Information Systems [PROMIS]), social (SSE) and emotional self-efficacy (ESE), loneliness, and Post-Traumatic Growth Inventory (PTGI) were administered at four timepoints (pre-/post-2024 and 2025 retreat). Quantitative data were analyzed with orthogonal polynomial contrasts and the MIXED procedure method. Qualitative survivor feedback was collected after the retreats. Counselor journals, participant quotes, and exit interviews were used to contextualize survivor-reported data. Results: PROMIS, SSE, and ESE improved immediately following the retreats, with continual improvement after the second retreat. PTGI did not change. After each retreat, AYAs scored the improvement in loneliness (7.3 ± 1.3 and 7.5 ± 1.9, respectively, with 10 representing maximal benefit), indicating that each retreat impacted their loneliness to the same degree. Qualitative data indicate that AYAs appreciated the opportunity to face difficult topics in a safe space and could benefit from attending consecutive retreats. Conclusion: The intervention benefited participants who were in different stages of their cancer and life journey and reached an underserved minority population. Implementation of these types of support groups could reduce loneliness and improve self-efficacy, thereby having broader impacts on quality of life.